The Impact of Social Media Sites on Deviant Behavior in University Youth "Descriptive Study on X-Platform Users" - Ahmed O. K. Hosnia, Mohamed Mohamed Basiouny Kandil, Shihab Sulaiman Abdalla Osman, Hanan Abdel Moniem Gubara Elbashir (Journal of Daoist Studies, 2026)
This study aims to analyze the impact of using the X platform on deviant behavior among university youth at Dhofar University in the Sultanate of Oman. The study based on the descriptive and analytical approaches, drawing on imitation theory as a theoretical framework, and was applied to a purposive sample of (115) male and female students. The results showed that the level of impact of using the X platform on deviant behavior was high. The most influential dimensions were celebrity imitation (high), followed by the spread of fake news (high), while the impact of cyberbullying was moderate. The study also found statistically significant differences in the level of impact in favor of males and in favor of students from the Faculty of Arts and Applied Sciences. The study found the necessity of adopting high-level preventive mechanisms, including imposing censorship on offensive and misleading content, establishing clear laws and regulations to control digital behavior and determine responsibilities to ensure deterrence. Keywords: social media, deviant behavior, university youth, X platform, online behavior.